Striving for excellence in ventilator bundle compliance through continuous quality improvement initiative in the intensive care unit of a tertiary care hospital in India - Naveen Paliwal; Pooja Bihani; Rishabh Jaju; Sadik Mohammed; Prabhu Prakash; Vidya Tharu (Acute and Critical Care, 2024)
Background Ventilator-associated pneumonia (VAP) is a significant nosocomial infection in intensive care units (ICUs). Ventilator bundle (VB) implementation has been shown to decrease the incidence of VAP. This study presents a 1-year quality improvement (QI) project conducted in the ICU of a tertiary care hospital with the goal of increasing VB compliance to greater than 90% and evaluating its impact on VAP incidence and ICU length of stay. Methods A series of Plan-Do-Study-Act (PDSA) cycles, including educational boot camps, checklist implementation, and simulation-based training, was implemented. Emphasis on standardization and documentation for each VB component further improved compliance. Data were compared using a chi-square test, unpaired t-test, or Mann-Whitney U-Test, as appropriate. A P-value <0.05 was considered statistically significant. Results The initial observed compliance was 40.7%, with a significant difference between knowledge and implementation. The compliance increased to 90% after the second PDSA cycle. In the third PDSA cycle, uniformity and standardization of all components of VAP were ensured. After increasing the VB compliance at greater than 90%, there was a significant decline in the incidence of VAP, from 62.4/1,000 ventilatory days to 25.7/1,000 ventilatory days, with a 2.34 times risk reduction in the VAP rate (P= 0.004) Conclusions The study highlights the effectiveness of a structured QI approach in enhancing VB compliance and reducing VAP incidence. There is a need for continued education, protocol standardization, and continuous monitoring to ensure the sustainability of this implementation.